2006
DOI: 10.1186/1465-9921-7-106
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance lung function – a breakthrough for lung imaging and functional assessment? A phantom study and clinical trial

Abstract: Background: Chronic lung diseases are a major issue in public health. A serial pulmonary assessment using imaging techniques free of ionizing radiation and which provides early information on local function impairment would therefore be a considerably important development. Magnetic resonance imaging (MRI) is a powerful tool for the static and dynamic imaging of many organs. Its application in lung imaging however, has been limited due to the low water content of the lung and the artefacts evident at air-tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 18 publications
3
104
0
Order By: Relevance
“…In the second approach, low-field imaging is performed at or below 0.5 Tesla in which susceptibility artifacts are within acceptable ranges due to the lower field strength. The limited signalto-noise ratio is balanced by thicker slices of up to 55 mm [16]. Since the information contained in thick slices is averaged into one image, this technique is, to a certain extent, more comparable with radiography, where all the information is averaged into one image.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the second approach, low-field imaging is performed at or below 0.5 Tesla in which susceptibility artifacts are within acceptable ranges due to the lower field strength. The limited signalto-noise ratio is balanced by thicker slices of up to 55 mm [16]. Since the information contained in thick slices is averaged into one image, this technique is, to a certain extent, more comparable with radiography, where all the information is averaged into one image.…”
Section: Discussionmentioning
confidence: 98%
“…The major advantage of high-field MRI is the possibility to assess structural information together with functional information, e.g., local ventilation, in one examination [16,35], thereby reducing imaging costs and increasing patient compliance. In two recent studies, hyperpolarized 3-helium MRI has been successfully investigated in comparison with PFT in children [36] and in comparison with spirometry and high-resolution CT in adults [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of proton MR imaging has historically been hampered by the combination of low proton density and short T2* of lung tissue (14,15), but it has regained attention with the development of short-acquisition-time techniques (16,17) and frequency-swept nuclear MR (18). Enhanced techniques developed with free-breathing MR imaging have been proposed to assess regional ventilation by using Fourier decomposition (19,20) and by using image registration (21,22).…”
Section: Study Subjectsmentioning
confidence: 99%
“…Bankier et al described multiple inversion recovery turbo spin‐echo sequence with the shortest possible TE (4.2 msec) for imaging human lungs and demonstrated that the gravity‐dependent gradients of MR signal changed in different postures, in which the signal represented the parenchymal tissue/blood density (19). Using a true fast imaging with steady state precession with TE of 2 msec, Zapke et al reported that the quantification of the change in the parenchymal signal during respiratory cycle could be a diagnostic tool for the pulmonary disorders (20). Recently, Failo et al showed the correlation in diagnostic quality between “very‐short” pulse repetition time (TR)/TE (TE of 800 μsec) two‐dimensional steady state free precession MRI and CT in patients with cystic fibrosis (21).…”
mentioning
confidence: 99%